2006
DOI: 10.1002/poc.1035
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range polar and steric effects in propionate‐SG1‐type alkoxyamines (SG1‐CHMeCOOX): a multiparameter analysis

Abstract: The effects of the substituent X on the homolysis rate constants (k d ) of SG1-propionate type alkoxyamines (SG1-CHMeCOOX) are analyzed by a multiparametric equation with y, the steric constant and s I , the polar inductive/field Hammett constant of X. An influence of long-range polar and steric effects on k d was observed, that is, decrease in k d with increasing size of the X group and increase in k d with increasing polarity of the X group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Furthermore, no differences in positive or negative charge distribution are noted between 1 b, 1 e, 1 g, 2, 2', and 5 ( Table 4). Because of the steric hindrance and electrostatic interactions, the carboxylic groups for the RS/SR diastereoisomers of 1 b, 1 e, 1 g, 2, and 2' are turned toward the phosphoryl group, whereas for the other diastereisomers they are in a position opposite both to the tBu and the phosphoryl groups (see Figures 5 and 6, and hC 7 C 6 O 5 N 4 i in Table 3) A recent study [22,31] showed that the difference in k d for the diastereoisomers of 5 is due to an anchimeric interaction which depends on the torsion angle hO 5 C 6 C 7 O 10 i (see Figure 7). Calculations for 2 and 1 b showed that the difference between these angle values and those of 5 is small.…”
Section: Dft Calculations and Nbo Analysismentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, no differences in positive or negative charge distribution are noted between 1 b, 1 e, 1 g, 2, 2', and 5 ( Table 4). Because of the steric hindrance and electrostatic interactions, the carboxylic groups for the RS/SR diastereoisomers of 1 b, 1 e, 1 g, 2, and 2' are turned toward the phosphoryl group, whereas for the other diastereisomers they are in a position opposite both to the tBu and the phosphoryl groups (see Figures 5 and 6, and hC 7 C 6 O 5 N 4 i in Table 3) A recent study [22,31] showed that the difference in k d for the diastereoisomers of 5 is due to an anchimeric interaction which depends on the torsion angle hO 5 C 6 C 7 O 10 i (see Figure 7). Calculations for 2 and 1 b showed that the difference between these angle values and those of 5 is small.…”
Section: Dft Calculations and Nbo Analysismentioning
confidence: 95%
“…31 P NMR studies of 1 a in C 6 D 6 revealed only one peak, whereas two peaks, corresponding to the two diastereoisomers, were observed in [D 6 ]DMSO (DMSO = dimethyl sulfoxide). For the alkoxyamines 1 a-f, the 31 P NMR shifts are clearly different from those of the starting material 2 and characteristic for each salt (see Table 2 and Experimental Section).…”
Section: Preparation Of the Alkoxyaminesmentioning
confidence: 95%
See 3 more Smart Citations